Qaryah Thayyibah Program Melalui Sosialiasi Pengurangan Dampak Ancaman Meteorologis pada Masyarakat Nelayan Kepulauan Masalembu - Furaida, Asni; Rusli, Rusli (JRCE (Journal of Research on Community Engagement), 2023)
Incidents of boats and fishing boats sinking in the waters of Masalembu often occur. These accidents were caused by bad weather. Therefore, it is necessary to disseminate information on reducing the impact of meteorological threats on the fishing community of Masalembu. Activities implemented by introducing the meteorological threats that have been faced so far, ranging from rain accompanied by strong winds, hurricanes, big waves and lightning. Another activity is helping fishermen to access weather information provided by the Maritime BMKG website both daily and weekly. It is hoped that the fishermen of the Masalembu islands can prepare and anticipate meteorological threats that are and will occur.